The Application of Nano Drug Delivery Systems in Female Upper Genital Tract Disorders - Daniélle van Staden; Minja Gerber; Hendrik J. R. Lemmer (Pharmaceutics)
The prevalence of female reproductive system disorders is increasing, especially among women of reproductive age, significantly impacting their quality of life and overall health. Managing these diseases effectively is challenging due to the complex nature of the female reproductive system, characterized by dynamic physiological environments and intricate anatomical structures. Innovative drug delivery approaches are necessary to facilitate the precise regulation and manipulation of biological tissues. Nanotechnology is increasingly considered to manage reproductive system disorders, for example, nanomaterial imaging allows for early detection and enhances diagnostic precision to determine disease severity and progression. Additionally, nano drug delivery systems are gaining attention for their ability to target the reproductive system successfully, thereby increasing therapeutic efficacy and decreasing side effects. This comprehensive review outlines the anatomy of the female upper genital tract by highlighting the complex mucosal barriers and their impact on systemic and local drug delivery. Advances in nano drug delivery are described for their sustainable therapeutic action and increased biocompatibility to highlight the potential of nano drug delivery strategies in managing female upper genital tract disorders.